Eco-Industrial Parks: Experiences from Turkey - Deniz Dolgen; M Necdet Alpaslan (Global Journal of Ecology - Peertechz Publications, 2020)
The development of Eco-Industrial Parks (EIPs) is an emerging concept that is being spread in Turkey as a sustainable development model. This study analyzes the improvement of EIPs in Turkey and discusses prevailing problems on transferring Organized Industrial Zones (OIZ) to EIPs. In the study, EIP projects completed by the Ministry of Science, Industry and Technology (MoSIT) and other institutions such as Regional Development Agencies, Technology Development Foundation of Turkey (TTGV), Universities, etc. are reviewed. The findings have shown that the potential for the application of EIPs is high in Turkey; however, there are various constraints on implementation. Some of these barriers are organizational and institutional setups, lack of interest of companies, deficiencies on financial sources, inadequate sharing of the good practices and absence of internationally accepted standards. The project titled as "Green OIZ Framework Development for Turkey" was customized to identify a comprehensive Green OIZ criterion, supported by MoSIT and assisted by the World Bank Group (WBG). This project evaluated the existing regulatory framework to create a roadmap for Green OIZs in Turkey. The performance requirements were considered in four key categories, namely, park management performance; environmental performance; social performance; and economic performance. Then, the sustainability criteria for the Turkish OIZs were proposed; however, further work is needed to tailor it and set the targets for the OIZs.